BEYOND SERVICE QUALITY: TRUST-BASED LOYALTY IN BEAUTY CLINIC SERVICES - Patwayati Patwayati; Agussalam Syahrir; Adwi Adwi (Journal of Information Systems Management and Digital Business, 2026)
Customer loyalty has become a critical issue in beauty clinic services, where customers evaluate not only service performance but also the credibility, safety, and trustworthiness of the provider. This study examines the effects of service quality and customer trust on customer loyalty among beauty clinic customers in Kendari, Indonesia. Drawing on service quality theory and relationship marketing theory, this study positions service quality as a functional evaluation mechanism and customer trust as a relational confidence mechanism in explaining customer loyalty. A quantitative survey was conducted involving 77 beauty clinic customers, and the data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. The findings show that both service quality and customer trust positively contribute to customer loyalty. Customer trust has a stronger effect than service quality, indicating that loyalty in beauty clinic services is shaped more by customers’ confidence in the clinic’s competence, honesty, safety, and care orientation than by service performance alone. The theoretical contribution of this study lies in extending service marketing literature by demonstrating that customer loyalty in risk-sensitive and experience-based services is better explained through the integration of functional service evaluation and relational trust. Practically, the findings suggest that beauty clinic managers should strengthen customer retention strategies by improving service quality while prioritizing transparent communication, professional competence, safe procedures, and consistent trust-building practices.